Perempuan Korban Kekerasan Berbasis Gender Online dan Perlindungan Hukumnya - Kayus Kayowuan LewoLeba; Mulyadi; Yuliana Yuli Wahyuni (UNES Law Review, 2023)
Seeing from the historical side, violence is one of the oldest social problems, which may be as old as human civilization, this is understandable because basically humans are homo homini lupus creatures, referring to the thoughts of the famous philosopher Aristotle, that humans can become wolves for others, can become "cannibals" in the sense that in certain situations humans can commit acts of violence against others both in physical and psychological forms. One form of violence that has been a serious problem for a long time is gender-based violence, especially against vulnerable groups, namely women. The phenomenon of violence against women is a global issue that continues to be discussed in various forums on a domestic, regional and international scale. Gender-based violence does not only target women, but can also occur in several other groups such as men, transgender or LGBT people. However, statistically, it does happen more to women. Gender-based violence targeting women is an act of terror against women that occurs quite a lot in various parts of the world Online Gender-Based Violence (GBV) has become a global phenomenon that is happening along with the progress and increased access to internet-based communication technologies. This research is a normative legal research that is reinforced with primary data to sharpen analysis. The results show that the forms of gender-based violence against women are cyber grooming, cyber harassment, hacking, illegal content, infringement of privacy, threat of personal photo/video distribution (malicious distribution), online defamation, and online recruitment. Legal protection for women victims of online gender-based violence refers to the regulations stipulated in the PKDRT Law, ITE Law, Child Protection Law, Pornography Law and TPKS Bill.